PENGARUH ELECTRONIC WORD OF MOUTH PADA MEDIA SOSIAL YOUTUBE DAN ASOSIASI MEREK TERHADAP MINAT BELI DENGAN CITRA MEREK SEBAGAI VARIABEL MEDIASI PADA PRODUK LAPTOP ASUS (Studi pada Mahasiswa Universitas Diponegoro Semarang) - Dionisius Bayu Dewantara; Susilo Toto Raharjo (Faculty of Economics and Business Diponegoro University, 2022)
The rapid development in the field of technology over the past few years has made humans a new perspective in terms of searching for information. Along with these developments, many companies and producers of goods or services are competing to make potential consumers interested in buying their products. One such company is ASUSTek Computer Inc. especially in its laptop product line. In the world market share, products from Asus do not enter the top five. In contrast to the market share in Indonesia, Asus ranks first in 2021 with 43.59%, outperform its competitors in Indonesia. This study aims to analyze the effect of electronic word of mouth on Youtube social media and brand associations on purchase intention with brand image as a mediating variable on Asus laptop products. The population in this study were students of Diponegoro University, Semarang. The number of samples in this study was 165 respondents. In this study, the method used is the Structural Equation Model (SEM) with the tool to be used is AMOS 25. The results of this study indicate that electronic word of mouth on Youtube social media has a positive and significant effect on brand image, brand association has a positive and significant effect on brand image, electronic word of mouth on social media Youtube has a positive and significant effect on purchase intention, brand associations have an effect positive and significant effect on purchase intention, and brand image has a positive and significant effect on purchase intention